Analysis of digital financial literacy and social environment on the interest in using e-money among college students - Zebua, Yuniman; Rambe, Sukma Hoviva (Social Sciences Insights Journal, 2024)
Most of the use of e-money for Indonesians is a legal tender for the primary transactions in Indonesian business activities. The purpose of the study was to determine the partial and simultaneous effects of whether digital financial literacy and social environment variables are the most successful variables affecting interest in using e-money. The sample in the study of students in Semesters II and IV of the Management Study Program, Faculty of Economics and Business, Labuhanbatu University, amounted to 81 people after being calculated by the Slovin formula. This study adopts multiple linear regression analysis. The results of this study, partially and simultaneously, show that the variables of digital financial literacy and social environment affect the interest in using e-money among Semester II and IV students of the Management Study Program of the Faculty of Economics and Business, Labuhanbatu University.